Isolation and characterization of plastic-degrading bacteria from garbage soil of Calajunan dumpsite, Mandurriao, Iloilo City. - Tayona, John Mark G.
Microbial biodegradation is seen as a tangible alternative to recycling as a means of controlling the amassing plastic wastes in the environment, and bacteria are among the microorganisms that are capable of degrading a wide array of plastics especially polythylene. This study generally aimed to isolate and characterize plastic-degrading bacteria from garbage soil of Calajunan Dumpsite, mandurriao, Iloilo City. Its specific objectives were: 1) to calculate the average weight reduction of the sample commercial biodegradable high density polyethylene (HDPE) plastic strips after 21 days of treatment with the isolates using residual weight recovery method, and 2) to compare and assess among the treatments the extent of plastic biodegradation and the isolates' biodegrading capabilities after the incubation period. Nine species of Bacillus spp. and one unidentified bacterial species, Isolate Cd1S2, all Gram-positive and endospore-froming, were isolated and characterized from the site. The highest average weight reduction or biodegradability of 2.3 x 10-2 g or 46 percent was calculated from Treatment E (HDPE + B. Cd1S5) while the lowest was 1.0 x 10-3 g or 2 percent in Treatment F (HDPE + B. sp. Cd2S1), G (HDPE + B. sp. Cd2S3), and H (HDPE + B. sp. Cd2S3). The t-test showed that there was a significant difference in biodegradation among the treatments and that all the isolates were capable of biodegrading the plastic strips at different rates in 21 days of incubation at 37 degrees centigrade.